Prevalence of non classical congenital adrenal hyperplasia due to 21‐hydroxylase deficiency in Greek women with acne: a hospital‐based cross‐sectional study. (15th June 2012) - Trakakis, E.; Papadavid, E.; Dalamaga, M.; Koumaki, D; Stavrianeas, N.; Rigopoulos, D.; Creatsas, G.; Kassanos, D.
Abstract Aim To determine the prevalence and frequency of non classical congenital adrenal hyperplasia (NC‐CAH) due to 21‐OHD at the time of clinical presentation and at the peripubertal period in a substantial sample of Greek women with acne and to investigate the correlation of serum T, 17‐OHP and DHEA‐S with acne appearance at the time of clinical presentation. Methods One hundred and twenty‐three unselected women with hyperandrogenemic symptoms were examined. After the ACTH stimulation test, 6 (4.9%) women were diagnosed with NC‐CAH due to 21‐OHD. Results There was not any statistical significant difference in the frequency of peripubertal acne between NC‐CAH group of patients (6.4%) and patients with hyperandrogenemia of other aetiology (93%), mainly ovarian (P = 0.41). However, there was a statistical significant difference in the prevalence of acne at the time of clinical examination between the two groups (P = 0.04). Acne was present in 83.3% of women with NC‐CAH vs. 41.02% of women in the hyperandrogenic group without NC‐CAH. A statistically significant decrease of acne from the peripubertal time to the time of clinical examination in the group of women with hyperandrogenemia of other aetiology (−21.37%) was observed compared to women with NC‐CAH (P < 0.001). Conclusion We have shown that acne persists from peripubertal period to adult life in NC‐CAH women whereas it tends to diminish in women with hyperandrogenemia of other aetiology. Acne is a prominent finding in women with NC‐CAH. Serum concentrations of 17‐OHP after ACTH stimulation (17‐OHP6O) should be investigated in women with persistent acne in adult life.